Eco-Physiological Study of Native Atriplex halimus L. for Purpose of Sand Fixation Seed Germination and Seedlings’ Development - Sharash, Omar; Alaib, Mohamad Adrawi (Al-Mukhtar Journal of Sciences, 2002)
The aim of this research is to investigate seed germination and seedlings’ development in native Atriplex halimus for possible use in plantation processes in arid and semiarid zones. The study divided in to two parts: Laboratory experiments including the effects of dark, light duration, water soaking and different concentrations of sodium chloride (NaCl) on germination. Field experiments including the effects of soil type on germination and seedlings; development. Three types of soil were used; peatmoss; sand and mixture (sand and peatmoss 2: 1). For laboratory experiments, the results showed that seeds were not photodormant as it was shown there was no effect of light on germination. Also soaking of fruits in water had no effect on total percentage of germination, but it accelerated the process of germination. Sodium chloride (NaCl) decreased the percentage of germination with increased concentrations. For field experiments, the results showed that soil type had no effect on seed germination. Seedlings’ development however to be very sensitive to soil type. Results reveald that the peatmoss was the best and sand was that least suitable for seedlings’ development.